Wave forces limit the establishment of submerged macrophytes in large shallow lakes. (9th June 2015) - Van Zuidam, Bastiaan G.; Peeters, Edwin T. H. M.
Abstract: We studied the effect of waves on submerged macrophytes and hypothesized that exposure to large wave forces can hamper seedling establishment. In an indoor experiment in cylindrical mesocosms we tested whether large wave forces indeed inhibited the establishment of Chara globularis and Potamogeton pusillus from the propagule bank. We mimicked the effect of wave forces by generating a circular flow that caused resuspension of the sediment. Four treatments were applied, consisting of different repetition frequencies of resuspension events. Emergence and early growth of both species were monitored over 8 weeks. The resuspension treatments significantly reduced the emergence of both species, by 91% and 45% on average for Chara sp. and P. pusillus, respectively. We analysed field observations on the two species in the lakes of the IJsselmeer area in the Netherlands to evaluate whether wave forces may also inhibit establishment of macrophytes in the field. The field data seemed to support the hypothesis as both species hardly occurred in areas where a large bottom shear stress had occurred in spring, according to simulations with the SWAN wave model. The calculated maximum bottom shear stress correlated well with the occurrence of both Chara sp. and P. pusillus in the field. Regressions showed that this effect of wave forces was additional to the effect of light availability. Our study indicates that large wave forces may inhibit the establishment of macrophytes in large lakes. Reducing large wave forces can therefore potentially promote macrophyte development in these large lakes.